Analysis of students' ideas and conceptual artifacts in knowledge‐building discourse. (31st May 2020) - Oshima, Jun; Oshima, Ritsuko; Saruwatari, Shunsuke
Abstract: This study proposes a new methodological approach to evaluate students' knowledge‐building discourse. First, we discuss the knowledge–creation metaphor of learning. In the metaphor, theories mention that learners should consider their collective knowledge objects or artifacts that materialize as a result of their collaborative discourse. Second, we argue the necessity of developing new analytics to evaluate student learning. We describe how students' ideas and their conceptual artifacts can be examined in discourse analysis. Third, we demonstrate the application of our analytics to real discourse data. We conducted a new type of social network analysis of discourse to examine how students continuously improve their ideas. Further, we conducted another network analysis of discourse, called the Epistemic Network Analysis, by coding students' epistemic actions as conceptual artifacts to create and examine their ideas.